Experimental study on mechanical properties of hybrid metal matrix composites using stir casting process. (2021) - Chitharthan, S.; Divakar, S.; Thalaieswaran, S.
Abstract: A widespread consent of particulate MMC for manufacturing process was because of the high production cost of components for conventional materials. The current study is targeted to explore the mechanical properties, corrosive behaviour and tribological property of LM13 reinforced with Aluminium Oxide (Al2 O3 ) and Boron Carbide (B4 C) with a varying weight percentage of reinforcement particles. The otcome discloses that the strength of hybrid MMC has increased up to 21.3% by increasing the percentage of Alumina by addition of boron carbide (B4 C) the hardness increases by 15.65% and the wear rate decreases by 28.63% the stir casting process parameters were varied and the optimal stir casting process parameters was obtained by Taguchi quality design concept.